Impelementasi Program Kerja Ekstrakurikuler Podcast Dalam Meningkatkan Keterampilan Public Speaking Peserta Didik Di SMP Negeri 1 Kayangan - Lestari, Dewi; Arianti, Resi (Jurnal Pengabdian Masyarakat Sains Indonesia (Indonesian Journal Of Science Community Services), 2023)
The Teaching Campus Program is an activity carried out to assist teachers in carrying out learning, especially training students' skills in public speaking. By following the Teaching Campus Program, the leadership spirit and character development of students will be honed. The purpose of this work program is (1) describing the implementation of podcast extracurricular in the teaching campus program (2) Describing the improvement of students' public speaking skills through Podcast extracurricular. The methods used are observation, discussion, direct practice through coaching. The result of the implementation of this work program is that SMP Negeri 1 Kayangan has an extracurricular that can be continued and produces students who excel in the field of public speaking, become a forum for students to develop their potential, especially public speaking skills. So it can be concluded that with this program the extracurricular podcast work program can be carried out, with the holding of the work program students who have an interest in hosts and public speaking can be more developed and useful in the future because public speaking is the ability to communicate verbally in front of many people with The purpose of conveying an information clearly, efficiently, and can be easily accepted by the listener. Keywords: Podcast, Public Speaking, Literacy.